Brand Evaluation and Consumers' Preference towards Pioneer and Follower Brands: Empirical Study on Dairy Products - Syahlani, SP; Rahmadi, PN; Haryadi, FT (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2011)
Abstract. The aims of this research were to identify brand recall as well as to analyze consumers? attitude and consumers? preference toward pioneer and follower brands on processed dairy product. One hundred and fifty housewives were engaged as respondents in this research. The techniques used in the data analysis were non parametric two related sample test, one sample t-test and independent sample t-test. The result indicated that each of the product category, the percentage of the pioneer brand preference was higher than follower brand, namely Ultra Milk (87.30%), Yakult (94.70%), Anlene (93.30%) and Kraft (98.70%). The result showed that from 150 respondents were able to correctly recall Ultra Milk (66.70%), Yakult (86.70%), Anlene (82.70%) and Kraft (96.00%) as the pioneer brand on each product category. Furthermore, the results showed that the average consumer attitudes were higher toward the pioneer brands than the follower brands. The result also indicated that consumers preferred pioneer brands than follower brands for the same flavour, quality and price. The result led to conclusion that consumers retrieved or recalled pioneer brands more correctly than follower brands. Moreover, consumers had a more favourable attitude to pioneer brands than to follower brands, in which consumers preferred to purchase the pioneer brands products to those of the follower brands concerning the farm-manufactured products of UHT milk, pro-biotic milk, high-calcium milk and cheese.Key Words: brand retrieval, brand recall, attitudes, preference